The Intelligibility of Interrupted Speech: Cochlear Implant Users and Normal Hearing Listeners - Bhargava, Pranesh (J Assoc Res Otolaryngol, 2016)
Compared with normal-hearing listeners, cochlear implant (CI) users display a loss of intelligibility of speech interrupted by silence or noise, possibly due to reduced ability to integrate and restore speech glimpses across silence or noise intervals. The present study was conducted to establish the extent of the deficit typical CI users have in understanding interrupted high-context sentences as a function of a range of interruption rates (1.5 to 24 Hz) and duty cycles (50 and 75 %). Further, factors such as reduced signal quality of CI signal transmission and advanced age, as well as potentially lower speech intelligibility of CI users even in the lack of interruption manipulation, were explored by presenting young, as well as age-matched, normal-hearing (NH) listeners with full-spectrum and vocoded speech (eight-channel and speech intelligibility baseline performance matched). While the actual CI users had more difficulties in understanding interrupted speech and taking advantage of faster interruption rates and increased duty cycle than the eight-channel noise-band vocoded listeners, their performance was similar to the matched noise-band vocoded listeners. These results suggest that while loss of spectro-temporal resolution indeed plays an important role in reduced intelligibility of interrupted speech, these factors alone cannot entirely explain the deficit. Other factors associated with real CIs, such as aging or failure in transmission of essential speech cues, seem to additionally contribute to poor intelligibility of interrupted speech.